Microscopic insights into methane activation and related processes on Pt/Ceria model catalysts - Lykhach, Yaroslava; Staudt, Thorsten; Lorenz, Michael Peter Andreas; Streber, Regine; Bayer, Andreas; Steinrück, Hans-Peter; Libuda, Jörg (ChemPhysChem, 2010)
Ceria-based supported noble-metal catalysts release oxygen, which may help to reduce the formation of carbonaceous residues, for example during hydrocarbon reforming. To gain insight into the microscopic origins of these effects, a model study is performed under ultrahigh-vacuum conditions using single-crystal-based supported model catalysts. The model systems are based on ordered CeO (111) films on Cu(111), on which Pt nanoparticles are grown by physical vapor deposition. The growth and structure of the surfaces are characterized by means of scanning tunneling microscopy, and the electronic structure and reactivity are probed by X-ray photoelectron spectroscopy. Specifically, it is shown that the fully oxidized CeO thin films undergo slight reduction upon Pt deposition (CeO ). This effect is enhanced upon annealing (CeO ), thus indicating facile oxygen release and reverse spillover. The model system is structurally stable up to temperatures exceeding 700 K. The activation of methane is investigated using high-kinetic-energy CH (0.83 eV), generated by a supersonic molecular beam. It is shown that dehydrogenation occurs under rapid formation of CH or C species without detectable amounts of CH being formed, even at low temperatures (100 K). The released hydrogen spills over to the CeO support, which leads to the formation of OH groups. At 200 K and above, the OH groups start to decompose leaving additional Ce centers behind (CeO ). At up to 700 K, carbon deposits are quantitatively removed by reaction with oxygen, which is supplied by reverse spillover from the CeO film, thus leading to substantial reduction of the support ( CeO ). © 2010 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.
Keywords: cerium oxide; heterogeneous catalysis; methane dehydrogenation; supported catalysts; platinum